Corporate Responsibility to the Community: A Study of CSR Implementation of PT. AMM in Kutai Kartanegara - Alisalman, Muhamad; Mustangin, Mustangin; Gaza, Abdillah Gymnastiar; Pasha, Tito Amellya (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this study is to examine the implementation of CSR Programs at PT. AMM in empowering the poor to get out of poverty through solving unemployment problems. This research uses a qualitative research approach because it is in accordance with the purpose of the study, which is to examine more deeply the implementation of PT. AMM. Data collection in this study by interview, observation and document study methods. Data analysis in this study is data reduction, data presentation, and conclusions. Data validity checking techniques use source triangulation and triangulation techniques. The results showed that PT. AMM has a CSR program in empowering the people of Jempayan Village. In its implementation, the community is given catering and laundry business opportunities. This shows that PT. AMM has a role in providing job opportunities to the people of Jempayan Village in Kutai Kartanegara. So that people have their own income, which was previously an unemployed society.